2008
DOI: 10.1016/j.drugalcdep.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk behavior among patients with co-occurring bipolar and substance use disorders: Associations with mania and drug abuse

Abstract: Background-Bipolar and substance use disorders frequently co-occur, and both are associated with impulsivity, impaired judgment, and risk-taking.Objectives-This study aimed to: (1) describe the rates of HIV sexual and drug risk behaviors among patients with co-occurring bipolar and substance use disorders, (2) test whether acute mania, psychiatric severity, and drug severity independently predict HIV risk, and (3) examine the relationship between specific substance dependencies and sexual risk behaviors.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 37 publications
4
67
1
2
Order By: Relevance
“…A study about HIV transmission risk made in the United States with bipolar people found that less psychiatric severity, the presence of a recent manic episode and a greater frequency in the use of illegal drugs were significant predictor factors (Meade et al, 2008). Another study made with people with bipolar disorders and HIV+ (where 91 had an affective episode before being diagnosed with HIV) reported that the presence of more manic and depression symptoms was significantly associated with unsafe sexual intercourse.…”
Section: Risky Behavior By Type Of Severe Mental Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…A study about HIV transmission risk made in the United States with bipolar people found that less psychiatric severity, the presence of a recent manic episode and a greater frequency in the use of illegal drugs were significant predictor factors (Meade et al, 2008). Another study made with people with bipolar disorders and HIV+ (where 91 had an affective episode before being diagnosed with HIV) reported that the presence of more manic and depression symptoms was significantly associated with unsafe sexual intercourse.…”
Section: Risky Behavior By Type Of Severe Mental Illnessmentioning
confidence: 99%
“…They have also found a connection between use and a search for multiple sex partners (Coverdale et al, 1997), as well as occasional or unknown sex partners (Meade, Graff, Griffin & Weiss, 2008;Susser et al, 1995). A study made in the United States with adolescents undergoing psychiatric treatment where substance use was not the primary diagnosis revealed a close relation between cocaine and crack use with the presence of risky sexual behavior for HIV (Tolou-Shams, Ewing, Tarantino & Brown, 2010).…”
Section: Risky Behavior For Hiv Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those with substance abuse (SA) or SUD also have greater overall severity, with increased manic symptoms and psychosis (Van Rossum et al, 2009), longer time spent in affective episodes (Gaudiano et al, 2008;Strakowski et al, 2007), impaired functional impairment (Goetz, Tohen, Reed, Lorenzo, & Vieta, 2007), lower quality of life (Singh, Mattoo, Sharan, & Basu, 2005) and more HIV risk behaviours (Meade, Graff, Griffin, & Weiss, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…7 Un estudio realizado en Estados Unidos en población con TAB encontró que el mayor uso de sustancias psicoactivas, la menor gravedad psiquiátrica y la presencia de un episodio maniaco reciente eran factores predictores significativos para el riesgo de transmisión de VIH. 8 Por su parte, un estudio realizado en adolescentes nigerianos con bipolaridad encontró que la comorbilidad, principalmente con trastornos relacionados al uso de sustancias psicoactivas, se asoció significativamente con el comportamiento sexual de riesgo, especialmente en los varones. Asimismo, se identificó que la mayor frecuencia de prácticas religiosas y el tener padres casados por lo civil tienen un efecto protector de las prácticas sexuales de riesgo.…”
Section: Introductionunclassified